Transmitter And Receiver Design Of An Airborne Synthetic Aperture Radar - Chan, Yee Kit (2002)
An Airborne Synthetic Aperture Radar (SAR) sensor has been designed and developed by the Centre of Applied Electromagnetic, Multimedia University, Malaysia. It operates at 6G Hz with 20M hz bandwidth. The single polarisation VV mode for simple classification and multi-temporal change detection is employed. The airborne SAR is designed to operate at the height of 7500m with swath width of around 8500 m. This system will operate in stripmap mode with incidence angle of 50 degree. The spatial resolution is 10mX10m. It has a Radar Cross Section (RCS) dynamic range of 50 dB for measurement of various types of terrain. The cost and complexity are kept low through the use of commercially avaolable parts for most of RF components.